Associations of current diet with plasma and urine TMAO in the KarMeN study: direct and indirect contributions. Issue 11 (8th September 2017) - Krüger, Ralf; Merz, Benedikt; Rist, Manuela J.; Ferrario, Paola G.; Bub, Achim; Kulling, Sabine E.; Watzl, Bernhard
Abstract : Scope: Knowledge on the influence of current diet on trimethylamine‐N‐oxide (TMAO) levels in humans is still inconsistent. Thus, we aimed to investigate associations of current diet with urine and plasma TMAO levels and to determine the effect of different foods on TMAO variation. Methods and results: TMAO concentrations of 297 healthy individuals were assessed using 1 H‐NMR spectroscopy for 24 h urine collection and spot urine, and LC‐MS for plasma. Of 35 assessed food groups, those with a correlation of ρ >|0.15| with plasma or urine TMAO levels were further investigated in multivariate linear regression models showing current fish and (red) meat consumption as plausible dietary sources of TMAO. Overall, explained variance of TMAO levels by current diet and co‐variables (age, sex, lean body mass, glomerular filtration rate) was small. Associations with urine and plasma concentrations differed depending on the TMAO source. Fish consumption was associated with urine and plasma TMAO concentrations, whereas meat consumption was only associated with TMAO concentrations in plasma. Furthermore, associations of plasma TMAO concentration with fish consumption were two times stronger than with meat consumption. Conclusion: Meat and fish consumption differentially affects TMAO concentrations in body fluids. Only a small fraction of variance is explained by current diet. Abstract : The study examines associations of current diet with urine and plasma trimethylamine‐N‐oxide (TMAO) levels and the effect of different foods on TMAO variation. TMAO concentrations of healthy individuals from the cross‐sectional KarMeN study were assessed by NMR (24 h and spot urine) and LC‐MS (plasma). Associations with food groups were investigated by multivariate linear regression, and differed depending on the TMAO source. (Red) meat and fish intake differentially affects TMAO concentrations in body fluids. Only a small fraction of variance is explained by current diet and co‐variables.